Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

Comparative evaluation of deltamethrin concentration and exposure time-dependent susceptibility in pyrethroid resistant and susceptible populations of three major stored product insect pests - Çetin Mutlu; Jacqueline Abarca-Duran; William R. Morrison; Kun Yan Zhu; Georgina V. Bingham (Crop Protection, 2026)

Platinum-group element systematics in the North Atlantic Igneous Province: New insights from Northern Irish and Irish magmatism - Anna O. Morrison; Michael J. Stock; Mark R. Cooper; Jens C.Ø. Andersen; Hannah S.R. Hughes; Elliot J. Carter; Jack Beckwith; Iain McDonald; Andrew C. Kerr; Paul Mohr (Lithos, 2026)

The Matador Bug and Several Related Leaf-footed Bugs (Hemiptera: Coreidae) Accumulate Cyanogens From their Host Plants - Colin R. Morrison; Brian E. Sedio; Lawrence E. Gilbert; Justin C. Havird; Ummat Somjee (Journal of Chemical Ecology, 2026)

Investigating a Semiochemical-Based Mechanism for the Beneficial Activity of Sorghum Intercropped with Soybeans on Management of Popillia Japonica - Nicole B. Kucherov; Matthew C. Hetherington; Alison R. Gerken; William R. Morrison; Tania N. Kim (Journal of Chemical Ecology, 2026)

Targeted Profiling of Signaling Molecules in Papaver rhoeas L. Reveals that Onset and Control of Benzylisoquinoline Alkaloid Biosynthesis Corresponds with Cytokinins, Independent of Light - Zeynab Azimychetabi; Anna B. Kisiala; Erin N. Morrison; Scott C. Farrow; R. J. Neil Emery (Journal of Plant Growth Regulation, 2026)

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Insecticidal effect of deltamethrin, pyrethrin, and spinosad on metal and concrete surfaces on six species of stored product insects - Deanna S. Scheff; Codi Mueller; Alexus Delaney; William R. Morrison (Journal of Stored Products Research, 2026)

Drained Agricultural Peatlands as Persistent Carbon Sources: Implications for Carbon and Water Use Intensity in Food Production - Brenda D'Acunha; Chris D. Evans; Alanna Bodo; Hollie Cooper; Dafydd Egryn Crabtree; Alexander Cumming; Jennifer M. Rhymes; Daniel Rylett; Rebekka R. E. Artz; Ross Morrison (Global Change Biology, 2026)
Peatlands have the capacity to sequester large quantities of carbon and can therefore play an important role in climate change mitigation. However, anthropogenic activities alter their hydrological regimes, converting them from net CO 2 sinks into net sources. In England and elsewhere, lowland peatlands have been heavily drained and modified for agricultural land use, resulting in some of the most productive farmland in the UK. Estimates of CO 2 emissions and water use from the area are scarce, but these data are required to understand the consequences of maintaining agricultural output whilst simultaneously reducing GHG emissions. In this paper, we compiled a uniquely comprehensive dataset of CO 2 and H 2 O flux measurements from flux towers on cropped lowland peat, and coupled this with crop calorific values to estimate carbon and water use intensities of food production on peat. Our results showed that croplands on peat emitted 23.1 ± 10.4 ton CO 2 ha −1 y −1 (mean ± SD). Sites with peat depth > 40 cm emitted 25.1 ± 9.2 ton CO 2 ha −1 , while wasted peat sites emitted 11.8 ± 4.8 ton CO 2 ha −1 . Effective water table depth and organic carbon content were the main drivers of variation in annual net ecosystem production and ecosystem respiration across sites; crop type partly followed these gradients, so may not be a direct driver of variations in emissions. ET was less variable across site‐years and depended on the phenology of crop production. When considering CO 2 emissions and water use per calorie produced, lettuce and celery rotations were the most C and water use intensive crops, with values an order of magnitude larger than cereal crops. Overall, this paper highlights the scale of CO 2 emissions from managed peatlands and the importance of balancing GHG emissions and water use with ongoing food production from these economically important areas.

The effect of the presence of dead individuals with different susceptibility to phosphine in pitfall traps with four different stored product insect species - Maria K. Sakka; Marina Gourgouta; William R. Morrison; Michael J. Domingue; Christos G. Athanassiou (Crop Protection, 2026)

Influence of commodity type and temperature on the population growth of Trogoderma granarium Everts and Trogoderma variabile Ballion (Coleoptera: Dermestidae) - Georgia V. Baliota; William R. Morrison; Michael J. Domingue; Christos G. Athanassiou (Journal of Stored Products Research, 2026)

Purification techniques for oxygen isotope analysis of inorganic phosphate across environmental matrices: A cross-discipline review - Shin-Ah Lee; Spencer R. Moller; Amanda R. Chappel; Sydney Riemer; Gareema Dhiman; Ruth Blake; Elise S. Morrison (Journal of Environmental Management, 2026)

Odor Preference, Feeding, Survival, and Reproductive Fitness of the Invasive Larger Grain Borer Prostephanus Truncatus on Acorns of Three Native North America Oak Species - Qinglei Ming; Matthew Hetherington; Melanie Kessler-Mathieu; Bruna Mattioni; Michael Tilley; Donghai Wang; William R. Morrison; James F. Campbell; Kun Yan Zhu; Erin D. Scully (Journal of Chemical Ecology, 2025)

Efficacy of amorphous silica dust for use against Sitophilus granarius and Rhyzopertha dominica as a grain protectant - Hannah E. Quellhorst; Maria K. Sakka; Georgia V. Baliota; Christos G. Athanassiou; Kun Yan Zhu; William R. Morrison (Journal of Stored Products Research, 2025)

Long-term field trials assess temporal trends and growing season weather on soybean seed yield, nutrient composition and nitrogen dynamics - Yi Hu; Raju Y. Soolanayakanahally; Robert D. Guy; Xuyang Lu; Salim N. Silim; Elroy R. Cober; Malcolm J. Morrison (Plant and Soil, 2025)

Assessing wildfire potential in a coastal forest watershed, British Columbia, Canada - Daniel D.B. Perrakis; Kendrick J. Brown; Kimberly Morrison; Daniel R. Horrelt; Stephen W. Taylor (Forest Ecology and Management, 2025)

Clarifying the role of the resist–accept–direct framework in supporting resource management planning processes - Gregor W. Schuurman; Wylie Carr; Cat Hawkins Hoffman; David J. Lawrence; Brian W. Miller; Erik A. Beever; Jean Brennan; Katherine R. Clifford; Scott Covington; Shelley D. Crausbay; Amanda E. Cravens; John Gross; et al. (Conservation Biology, 2025)

Evaluating sulfurization as a blue carbon sink in a southern California salt marsh - Lena R. Capece; Melea Bailey; Max Morrison; Alexandra A. Phillips; Lewis Sharpnack; Sam M. Webb; Dana C. Brenner; Maya Gomes; Morgan R. Raven (Limnology and Oceanography, 2025)
Blue carbon ecosystems such as seagrass meadows, mangrove forests, and salt marshes are important carbon sinks that can store carbon for millennia. Recently, organic matter sulfurization and pyritization have been proposed as mechanisms of net carbon storage in blue carbon ecosystems. At our study site, organic sulfur that is resistant to acid hydrolysis (protokerogen) is an order of magnitude less abundant than pyrite sulfur, suggesting a dominance of pyritization over sulfurization. The C/N ratios and carbon isotope compositions suggest that nearly half of total organic carbon and ≥ 80% of protokerogen is composed of marsh plant material. Sediment protokerogen appears to be sulfurized based on its low δ 34 S values (− 10‰), abundance of disulfides, and higher S/C ratio (~ 1.0%) relative to potential biogenic sulfur sources. However, the interpretation of protokerogen δ 34 S values is complicated by the wide range in sulfur isotope compositions of marsh plants. Evidence for sulfurization occurs within the shallowest sediments across different vegetation zones, yielding consistent products, while pyritization appears to be more sensitive to alterations in sediment redox conditions. Based on organic sulfur and pyrite content, sulfurization may be a more spatially consistent process than pyritization, with implications for carbon storage. The relative abundance of pyrite and protokerogen organic sulfur indicates that pyritization is favored at our study site, but this is likely to vary across the spectrum of blue carbon ecosystems.

Prenatal PFAS exposures and cardiometabolic health in middle childhood in the MIREC cohort - Alan J. Fossa; Amber M. Hall; George D. Papandonatos; Tye E. Arbuckle; Jillian Ashley-Martin; Michael M. Borghese; Jenny Bruin; Aimin Chen; Mandy Fisher; John E. Krzeczkowski; Bruce P. Lanphear; Amanda J. MacFarlane; et al. (Environmental Research, 2025)

A synergist increases short-term efficacy of long-lasting insecticide-incorporated netting against pyrethroid-resistant maize weevil, Sitophilus zeamais - Sabita Ranabhat; Hannah E. Quellhorst; Brandon Black; Jaycob Andersen; Breck Aguinaga; Matthew C. Hetherington; Georgina V. Bingham; Kun Yan Zhu; William R. Morrison (Journal of Pest Science, 2025)

Spillage and food dust do not decrease efficacy of long-lasting insecticide-incorporated netting against stored product insects - Sabita Ranabhat; Çetin Mutlu; Georgina V. Bingham; Jennifer Abshire; Tanja McKay; Kun Yan Zhu; William R. Morrison (Journal of Stored Products Research, 2025)

Delayed recovery and sublethal effects on the semiochemical-mediated taxis by khapra beetle after exposure to long-lasting insecticide-incorporated netting - Sabita Ranabhat; Michael J. Domingue; Scott W. Myers; Kun Yan Zhu; William R. Morrison (Journal of Stored Products Research, 2025)

Intercropping Alters Phytochemicals Associated With Insect Herbivory - Jarrod Q. Fyie; Chase A. Stratton; William R. Morrison; Ebony G. Murrell (Journal of Chemical Ecology, 2025)

Nuance in the Narrative of a Brown Poison Frog: Environmental Alkaloids and Specialized Foraging in a Presumed Toxin-Free and Diet-Generalized Species - Jeffrey L. Coleman; Steven Y. Wang; Paul E. Marek; Colin R. Morrison; Brian E. Sedio; David C. Cannatella (Journal of Chemical Ecology, 2025)

Evidence of eastern rockhopper penguin feeding on a key commercial arrow squid species - Hugo R. Guímaro; David R. Thompson; Kyle W. Morrison; Joana Fragão; Ricardo S. Matias; José C. Xavier (Polar Biology, 2025)
Cephalopods are crucial to the Southern Ocean ecosystem, connecting top predators with mid-trophic organisms, yet their ecology in the Pacific sector is not well understood. This research used stable isotope analysis to explore the habitat and trophic ecology of cephalopods found in the diet of eastern rockhopper penguins ( Eudyptes chrysocome filholi ) around Campbell Island, a New Zealand sub-Antarctic island. Eastern rockhopper penguins were used as biologic samplers, revealing some differences in cephalopod diversity and ecology between two breeding seasons—1986–87 and 2012–13—, and the squid Nototodarus sloanii , a commercially valuable species, was described for the first time in the 2012–13 season. Stable isotope values ( δ 13 C and δ 15 N) for the squid species Moroteuthopsis ingens were consistent between seasons, indicating ecological stability, whereas the octopod species Octopus campbelli showed changes, suggesting shifts in habitat and feeding. Warmer oceanic temperatures in 2012–13 may have facilitated the emergence of N. sloanii on the diet of the eastern rockhopper penguins. These findings highlight potential changes in cephalopod biodiversity in the Pacific sector of the Southern Ocean, emphasizing the need for further research on ecological dynamics of this region.

Environmental drivers of tropospheric bromine and mercury variability in coastal East Antarctica - Neil C. Page; Jenny A. Fisher; Stephen R. Wilson; Robyn Schofield; Robert G. Ryan; Sean Gribben; Andrew R. Klekociuk; Grant C. Edwards; Anthony Morrison (Atmospheric Environment, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Sex-linked differences in semiochemical-mediated movement by Trogoderma variabile Ballion and Trogoderma inclusum LeConte (Coleoptera: Dermestidae) after exposure to long-lasting insecticide-incorporated netting - Sabita Ranabhat; Michael J. Domingue; Ian Stoll; Georgina V. Bingham; Kun Yan Zhu; William R. Morrison (Journal of Stored Products Research, 2024)

Nitrous oxide and methane fluxes from plasma-treated pig slurry applied to winter wheat - I. L. Lloyd; R. P. Grayson; M. V. Galdos; R. Morrison; P. J. Chapman (Nutrient Cycling in Agroecosystems, 2024)
The use of livestock waste as an organic fertiliser releases significant greenhouse gas emissions, exacerbating climate change. Innovative fertiliser management practices, such as treating slurry with plasma induction, have the potential to reduce losses of carbon and nitrogen to the environment. The existing research on the effectiveness of plasma-treated slurry at reducing nitrous oxide (N 2 O) and methane (CH 4 ) emissions, however, is not comprehensive, although must be understood if this technology is to be utilised on a large scale. A randomised block experiment was conducted to measure soil fluxes of N 2 O and CH 4 from winter wheat every two hours over an 83-day period using automated chambers. Three treatments receiving a similar amount of plant-available N were used: (1) inorganic fertiliser (IF); (2) pig slurry combined with inorganic fertiliser (PS); (3) plasma-treated pig slurry combined with inorganic fertiliser (TPS). Cumulative N 2 O fluxes from TPS (1.14 g N m −2 ) were greater than those from PS (0.32 g N m −2 ) and IF (0.13 g N m −2 ). A diurnal pattern in N 2 O fluxes was observed towards the end of the experiment for all treatments, and was driven by increases in water-filled pore space and photosynthetically active radiation and decreases in air temperature. Cumulative CH 4 fluxes from PS (3.2 g C m −2 ) were considerably greater than those from IF (− 1.4 g C m −2 ) and TPS (− 1.4 g C m −2 ). The greenhouse gas intensity of TPS (0.2 g CO 2 -eq kg grain −1 ) was over twice that of PS (0.07 g CO 2 -eq kg grain −1 ) and around six times that of IF (0.03 g CO 2 -eq kg grain −1 ). Although treating pig slurry with plasma induction considerably reduced CH 4 fluxes from soil, it increased N 2 O emissions, resulting in higher non-CO 2 emissions from this treatment. Life-cycle analysis will be required to evaluate whether the upstream manufacturing and transport emissions associated with inorganic fertiliser usage are outweighed by the emissions observed following the application of treated pig slurry to soil.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Population growth of two strains of the larger grain borer, Prostephanus truncatus on three maize hybrids grown in Europe - Hannah E. Quellhorst; Maria K. Sakka; William R. Morrison; Kun Yan Zhu; Christos G. Athanassiou (Crop Protection, 2024)

Governance of coastal wetlands: Beyond the community conservation paradigm - Mayara de Oliveira; Tiffany Morrison; Katherine R. O'Brien; Catherine E. Lovelock (Ocean & Coastal Management, 2024)

Floating debris and organisms can raft to Antarctic coasts from all major Southern Hemisphere landmasses - Hannah R. S. Dawson; Matthew H. England; Adele K. Morrison; Veronica Tamsitt; Ceridwen I. Fraser (Global Change Biology, 2024)
Antarctica's unique marine ecosystems are threatened by the arrival of non‐native marine species on rafting ocean objects. The harsh environmental conditions in Antarctica prevent the establishment of many such species, but warming around the continent and the opening up of ice‐free regions may already be reducing these barriers. Although recent genomic work has revealed that rafts—potentially carrying diverse coastal passengers—reach Antarctica from sub‐Antarctic islands, Antarctica's vulnerability to incursions from Southern Hemisphere continents remains unknown. Here we use 0.1° global ocean model simulations to explore whether drift connections exist between more northern, temperate landmasses and the Antarctic coastline. We show that passively floating objects can drift to Antarctica not only from sub‐Antarctic islands, but also from continental locations north of the Subtropical Front including Australia, South Africa, South America and Zealandia. We find that the Antarctic Peninsula is the region at highest risk for non‐native species introductions arriving by natural oceanic dispersal, highlighting the vulnerability of this region, which is also at risk from introductions via ship traffic and rapid warming. The widespread connections with sub‐Antarctic and temperate landmasses, combined with an increasing abundance of marine anthropogenic rafting vectors, poses a growing risk to Antarctic marine ecosystems, especially as environmental conditions around Antarctica are projected to become more suitable for non‐native species in the future.

Characterizing sulfur redox state and geochemical implications in deep-time using mineral chemistry network analysis - Eli K. Moore; Joseph E. Diedolf; Shaunna M. Morrison; Daniel R. Hummer (Geochimica et Cosmochimica Acta, 2024)

A circumpolar study unveils a positive non‐linear effect of temperature on arctic arthropod availability that may reduce the risk of warming‐induced trophic mismatch for breeding shorebirds - Aurélie Chagnon‐Lafortune; Éliane Duchesne; Pierre Legagneux; Laura McKinnon; Jeroen Reneerkens; Nicolas Casajus; Kenneth F. Abraham; Élise Bolduc; Glen S. Brown; Stephen C. Brown; H. River Gates; Olivier Gilg; et al. (Global Change Biology, 2024)
Seasonally abundant arthropods are a crucial food source for many migratory birds that breed in the Arctic. In cold environments, the growth and emergence of arthropods are particularly tied to temperature. Thus, the phenology of arthropods is anticipated to undergo a rapid change in response to a warming climate, potentially leading to a trophic mismatch between migratory insectivorous birds and their prey. Using data from 19 sites spanning a wide temperature gradient from the Subarctic to the High Arctic, we investigated the effects of temperature on the phenology and biomass of arthropods available to shorebirds during their short breeding season at high latitudes. We hypothesized that prolonged exposure to warmer summer temperatures would generate earlier peaks in arthropod biomass, as well as higher peak and seasonal biomass. Across the temperature gradient encompassed by our study sites (>10°C in average summer temperatures), we found a 3‐day shift in average peak date for every increment of 80 cumulative thawing degree‐days. Interestingly, we found a linear relationship between temperature and arthropod biomass only below temperature thresholds. Higher temperatures were associated with higher peak and seasonal biomass below 106 and 177 cumulative thawing degree‐days, respectively, between June 5 and July 15. Beyond these thresholds, no relationship was observed between temperature and arthropod biomass. Our results suggest that prolonged exposure to elevated temperatures can positively influence prey availability for some arctic birds. This positive effect could, in part, stem from changes in arthropod assemblages and may reduce the risk of trophic mismatch.

Distribution of logjams in relation to lateral connectivity in the River Corridor - Ellen Wohl; Anna E. Marshall; Shayla Triantafillou; Mattea Mobley; Mickey Means-Brous; Ryan R. Morrison (Geomorphology, 2024)

Structured decision making remains underused in ecological restoration despite opportunities - Morgan L. Piczak; Jessica A. Robichaud; Peter Morrison; Andrew M. Rous; Ingeborg M. Mulder; Cassandra J. Hill; Tanya S. Prystay; Hanna Rosner-Katz; Kelly F. Robinson; Joseph R. Bennett; Steven J. Cooke (Environment Systems and Decisions, 2024)

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

Saw-toothed grain beetle, Oryzaephilus surinamensis, an internationally important stored product pest - Marina Gourgouta; William R. Morrison; David W. Hagstrum; Christos G. Athanassiou (Journal of Stored Products Research, 2023)

Determining the response of riparian vegetation and river morphology to drought using Google Earth Engine and machine learning - Smriti Chaulagain; Mark C. Stone; Ryan R. Morrison; Liping Yang; Julie Coonrod; Noelani E. Villa (Journal of Arid Environments, 2023)

Algal blooms in a river-dominated estuary and nearshore region of Florida, USA: the influence of regulated discharges from water control structures on hydrologic and nutrient conditions - E. J. Phlips; S. Badylak; A. L. Mathews; E. C. Milbrandt; L. R. Montefiore; E. S. Morrison; N. Nelson; B. Stelling (Hydrobiologia, 2023)
Flow-regulated discharges of water from control structures into estuaries result in hydrologic and water chemistry conditions that impact spatial and temporal variability in the structure and biomass of phytoplankton communities, including the potential for harmful algal blooms (HABs). The relationships between regulated Caloosahatchee River (i.e., C-43 Canal) discharges and phytoplankton communities in the Caloosahatchee Estuary and adjacent nearshore regions on the southwest coast of Florida were investigated during two study periods, 2009–2010 and 2018–2019. During periods of low to moderate discharge rates, when mesohaline conditions predominated in the estuary, and water residence times were comparatively long, major blooms of the HAB dinoflagellate species Akashiwo sanguinea were observed in the estuary. Periods of high discharge were characterized by comparatively low phytoplankton biomass in the estuary and greater influence of a wide range of freshwater taxa in the upper reaches. By contrast, intense blooms of the toxic dinoflagellate Karenia brevis in the nearshore region outside of the estuary were observed during high discharge periods in 2018–2019. The latter events were significantly associated with elevated levels of nitrogen in the estuary compared to lower average concentrations in the 2009–2010 study period. The relationships observed in this study provide insights into the importance of managing regulated discharge regimes to minimize adverse impacts of HABs on the health of the estuary and related coastal environments.

Phytohormonal impacts on fatty acid profiles in Chlorella vulgaris Beijerinck: endogenous identification and exogenous application of cytokinins and abscisic acid - Kira Ramphal; Ainsely Lewis; Natasha A. Trzaskalski; Anna Kisiala; Erin N. Morrison; Suresh S. Narine; R. J. Neil Emery (Journal of Applied Phycology, 2023)

Cultivation of heterotrophic Euglena gracilis: The effects of recycled media on culture growth and associations with growth regulating phytohormone profiles - Alexandra M. Kuhne; Erin N. Morrison; Tamanna Sultana; Anna B. Kisiala; Kathleen Horlock-Roberts; Adam Noble; R. J. Neil Emery (Journal of Applied Phycology, 2023)

A global synthesis of peer‐reviewed research on the effects of hatchery salmonids on wild salmonids - John R. McMillan; Brian Morrison; Nick Chambers; Greg Ruggerone; Louis Bernatchez; Jack Stanford; Helen Neville (Fisheries Management and Ecology, 2023)
Hatcheries have long produced salmonids for fisheries and mitigation, though their widespread use is increasingly controversial because of potential impacts to wild salmonids. We conducted a global literature search of peer‐reviewed publications (1970–2021) evaluating how hatchery salmonids affected wild salmonids, developed a publicly available database, and synthesized results. Two hundred six publications met our search criteria, with 83% reporting adverse/minimally adverse effects on wild salmonids. Adverse genetic effects on diversity were most common, followed by effects on productivity and abundance via ecological and genetic processes. Few publications (3%) reported beneficial hatchery effects on wild salmonids, nearly all from intensive recovery programs used to bolster highly depleted wild populations. Our review suggests hatcheries commonly have adverse impacts on wild salmonids in freshwater and marine environments. Future research on less studied effects—such as epigenetics—could improve knowledge and management of the full extent of hatchery impacts.

Controls on the composition of dissolved organic matter in treatment wetland source waters of South Florida, USA - Joao Henrique F. Amaral; Jacob R. Gaddy; Thomas S. Bianchi; Todd Z. Osborne; Susan Newman; Jacob Dombrowski; Elise S. Morrison (Ecological Engineering, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Beyond ecology: ecosystem restoration as a process for social-ecological transformation - Anazélia M. Tedesco; Sofía López-Cubillos; Robin Chazdon; Jonathan R. Rhodes; Carla L. Archibald; Katharina-Victoria Pérez-Hämmerle; Pedro H.S. Brancalion; Kerrie A. Wilson; Mariana Oliveira; Diego F. Correa; Liz Ota; Tiffany H. Morrison; et al. (Trends in Ecology & Evolution, 2023)

Current State and Opportunities with Long-acting Injectables: Industry Perspectives from the Innovation and Quality Consortium “Long-Acting Injectables” Working Group - Andrea Bauer; Philippe Berben; Sudhir S. Chakravarthi; Sayantan Chattorraj; Ashish Garg; Betty Gourdon; Tycho Heimbach; Ye Huang; Christopher Morrison; Deepak Mundhra; Ramesh Palaparthy; Pratik Saha; et al. (Pharmaceutical Research, 2023)

Discovery of pyrrolo[2,1-f][1,2,4]triazine-based inhibitors of adaptor protein 2-associated kinase 1 for the treatment of pain - Carolyn D. Dzierba; Bireshwar Dasgupta; George Karageorge; Walter Kostich; Brian Hamman; Jason Allen; Kim M. Esposito; Ramesh Padmanabha; James Grace; Kimberley Lentz; John Morrison; Daniel Morgan; et al. (Medicinal Chemistry Research, 2023)

Effects of the pesticide deltamethrin on high fat diet-induced obesity and insulin resistance in male mice - Evangelia E. Tsakiridis; Marisa R. Morrow; Eric M. Desjardins; Dongdong Wang; Andrea Llanos; Bo Wang; Michael G. Wade; Katherine M. Morrison; Alison C. Holloway; Gregory R. Steinberg (Food and Chemical Toxicology, 2023)

A systematic literature review considering the implementation of planetary geoengineering techniques for the mitigation of sea-level rise - R. Minunno; N. Andersson; G.M. Morrison (Earth-Science Reviews, 2023)

Research priorities for the sustainability of coral-rich western Pacific seascapes - Graeme S. Cumming; Maja Adamska; Michele L. Barnes; Jon Barnett; David R. Bellwood; Joshua E. Cinner; Philippa J. Cohen; Jennifer M. Donelson; Katharina Fabricius; R. Quentin Grafton; Alana Grech; Georgina G. Gurney; et al. (Regional Environmental Change, 2023)
Nearly a billion people depend on tropical seascapes. The need to ensure sustainable use of these vital areas is recognised, as one of 17 policy commitments made by world leaders, in Sustainable Development Goal (SDG) 14 (‘Life below Water’) of the United Nations. SDG 14 seeks to secure marine sustainability by 2030. In a time of increasing social-ecological unpredictability and risk, scientists and policymakers working towards SDG 14 in the Asia–Pacific region need to know: (1) How are seascapes changing? (2) What can global society do about these changes? and (3) How can science and society together achieve sustainable seascape futures? Through a horizon scan, we identified nine emerging research priorities that clarify potential research contributions to marine sustainability in locations with high coral reef abundance. They include research on seascape geological and biological evolution and adaptation; elucidating drivers and mechanisms of change; understanding how seascape functions and services are produced, and how people depend on them; costs, benefits, and trade-offs to people in changing seascapes; improving seascape technologies and practices; learning to govern and manage seascapes for all; sustainable use, justice, and human well-being; bridging communities and epistemologies for innovative, equitable, and scale-crossing solutions; and informing resilient seascape futures through modelling and synthesis. Researchers can contribute to the sustainability of tropical seascapes by co-developing transdisciplinary understandings of people and ecosystems, emphasising the importance of equity and justice, and improving knowledge of key cross-scale and cross-level processes, feedbacks, and thresholds.

The dispersal ability of the invasive larger grain borer and the cosmopolitan maize weevil after brief exposure to a newer insecticide formulation - Hannah E. Quellhorst; Frank H. Arthur; Kun Yan Zhu; Alex Bruce; William R. Morrison (Journal of Stored Products Research, 2023)

Different trap designs and attractants affect the capture of multiple life stages of Trogoderma granarium Everts and Trogoderma variabile Ballion in the laboratory - Maria K. Sakka; Marina Gourgouta; William R. Morrison; Michael J. Domingue; Robert F. Grosdidier; Rachel V. Wilkins; Christos G. Athanassiou (Journal of Stored Products Research, 2023)

Coupling large-spatial scale larval dispersal modelling with barcoding to refine the amphi-Atlantic connectivity hypothesis in deep-sea seep mussels - Elodie Portanier; Amandine Nicolle; Willi Rath; Lorraine Monnet; Gregoire Le Goff; Anne-Sophie Le Port; Claire Daguin-Thiébaut; Cheryl L. Morrison; Marina R. Cunha; Melissa Betters; Craig M. Young; Cindy L. Van Dover; et al. (Frontiers in Marine Science, 2023)
In highly fragmented and relatively stable cold-seep ecosystems, species are expected to exhibit high migration rates and long-distance dispersal of long-lived pelagic larvae to maintain genetic integrity over their range. Accordingly, several species inhabiting cold seeps are widely distributed across the whole Atlantic Ocean, with low genetic divergence between metapopulations on both sides of the Atlantic Equatorial Belt (AEB, i.e. Barbados and African/European margins). Two hypotheses may explain such patterns: (i) the occurrence of present-day gene flow or (ii) incomplete lineage sorting due to large population sizes and low mutation rates. Here, we evaluated the first hypothesis using the cold seep mussels Gigantidas childressi, G. mauritanicus, Bathymodiolus heckerae and B. boomerang . We combined COI barcoding of 763 individuals with VIKING20X larval dispersal modelling at a large spatial scale not previously investigated. Population genetics supported the parallel evolution of Gigantidas and Bathymodiolus genera in the Atlantic Ocean and the occurrence of a 1-3 Million-year-old vicariance effect that isolated populations across the Caribbean Sea. Both population genetics and larval dispersal modelling suggested that contemporary gene flow and larval exchanges are possible across the AEB and the Caribbean Sea, although probably rare. When occurring, larval flow was eastward (AEB - only for B. boomerang ) or northward (Caribbean Sea - only for G. mauritanicus ). Caution is nevertheless required since we focused on only one mitochondrial gene, which may underestimate gene flow if a genetic barrier exists. Non-negligible genetic differentiation occurred between Barbados and African populations, so we could not discount the incomplete lineage sorting hypothesis. Larval dispersal modelling simulations supported the genetic findings along the American coast with high amounts of larval flow between the Gulf of Mexico (GoM) and the US Atlantic Margin, although the Blake Ridge population of B. heckerae appeared genetically differentiated. Overall, our results suggest that additional studies using nuclear genetic markers and population genomics approaches are needed to clarify the evolutionary history of the Atlantic bathymodioline mussels and to distinguish between ongoing and past processes.

Boundary-Layer Processes Hindering Contemporary Numerical Weather Prediction Models - Marc Calaf; Nikki Vercauteren; Gabriel G. Katul; Marco G. Giometto; Travis J. Morrison; Fabien Margairaz; Vyacheslav Boyko; Eric R. Pardyjak (Boundary-Layer Meteorology, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Trichoderma Synthesizes Cytokinins and Alters Cytokinin Dynamics of Inoculated Arabidopsis Seedlings - Kimberly Molina Bean; Anna B. Kisiala; Erin N. Morrison; R. J. Neil Emery (Journal of Plant Growth Regulation, 2022)

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

Data-driven approaches for runoff prediction using distributed data - Heechan Han; Ryan R. Morrison (Stochastic Environmental Research and Risk Assessment, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Responsible agriculture must adapt to the wetland character of mid‐latitude peatlands - Benjamin W. J. Freeman; Chris D. Evans; Samuel Musarika; Ross Morrison; Thomas R. Newman; Susan E. Page; Giles F. S. Wiggs; Nicholle G. A. Bell; David Styles; Yuan Wen; David R. Chadwick; Davey L. Jones (Global Change Biology, 2022)
Drained, lowland agricultural peatlands are greenhouse gas (GHG) emission hotspots and a large but vulnerable store of irrecoverable carbon. They exhibit soil loss rates of ~2.0 cm yr −1 and are estimated to account for 32% of global cropland emissions while producing only 1.1% of crop kilocalories. Carbon dioxide emissions account for >80% of their terrestrial GHG emissions and are largely controlled by water table depth. Reducing drainage depths is, therefore, essential for responsible peatland management. Peatland restoration can substantially reduce emissions. However, this may conflict with societal needs to maintain productive use, to protect food security and livelihoods. Wetland agriculture strategies will, therefore, be required to adapt agriculture to the wetland character of peatlands, and balance GHG mitigation against productivity, where halting emissions is not immediately possible. Paludiculture may substantially reduce GHG emissions but will not always be viable in the current economic landscape. Reduced drainage intensity systems may deliver partial reductions in the rate of emissions, with smaller modifications to existing systems. These compromise systems may face fewer hurdles to adoption and minimize environmental harm until societal conditions favour strategies that can halt emissions. Wetland agriculture will face agronomic, socio‐economic and water management challenges, and careful implementation will be required. Diversity of values and priorities among stakeholders creates the potential for conflict. Successful implementation will require participatory research approaches and co‐creation of workable solutions. Policymakers, private sector funders and researchers have key roles to play but adoption risks would fall predominantly on land managers. Development of a robust wetland agriculture paradigm is essential to deliver resilient production systems and wider environmental benefits. The challenge of responsible use presents an opportunity to rethink peatland management and create thriving, innovative and green wetland landscapes for everyone's future benefit, while making a vital contribution to global climate change mitigation.

Social environment during fear extinction alters the binding of [3H] MK-801 to N-methyl-D-aspartic acid receptors in Wistar-Kyoto and Wistar rats - Jamie K. DaSilva; Yanlin Lei; Adrian R. Morrison; Shanaz Tejani-Butt (Medicinal Chemistry Research, 2022)

Conventional versus drug-eluting embolic transarterial chemoembolization with doxorubicin: comparative drug delivery, pharmacokinetics, and treatment response in a rabbit VX2 tumor model - Ron C. Gaba; Ramzy C. Khabbaz; Ruth N. Muchiri; Joseph D. Morrison; Lobna Elkhadragy; William M. Totura; Jonathan P. Samuelson; Herbert E. Whiteley; Ryan L. Deaton; Peter L. Nguyen; Maria Sverdlov; Jeremy J. Johnson; et al. (Drug Delivery and Translational Research, 2022)

The Heat-Flux Imbalance: The Role of Advection and Dispersive Fluxes on Heat Transport Over Thermally Heterogeneous Terrain - Travis Morrison; Eric R. Pardyjak; Matthias Mauder; Marc Calaf (Boundary-Layer Meteorology, 2022)

Habitat‐linked genetic variation supports microgeographic adaptive divergence in an island‐endemic bird species - Rebecca G. Cheek; Brenna R. Forester; Patricia E. Salerno; Daryl R. Trumbo; Kathryn M. Langin; Nancy Chen; T. Scott Sillett; Scott A. Morrison; Cameron K. Ghalambor; W. Chris Funk (Molecular Ecology, 2022)
We investigated the potential mechanisms driving habitat‐linked genetic divergence within a bird species endemic to a single 250‐km 2 island. The island scrub‐jay ( Aphelocoma insularis ) exhibits microgeographic divergence in bill morphology across pine–oak ecotones on Santa Cruz Island, California (USA), similar to adaptive differences described in mainland congeners over much larger geographic scales. To test whether individuals exhibit genetic differentiation related to habitat type and divergence in bill length, we genotyped over 3000 single nucleotide polymorphisms in 123 adult island scrub‐jay males from across Santa Cruz Island using restriction site‐associated DNA sequencing. Neutral landscape genomic analyses revealed that genome‐wide genetic differentiation was primarily related to geographic distance and differences in habitat composition. We also found 168 putatively adaptive loci associated with habitat type using multivariate redundancy analysis while controlling for spatial effects. Finally, two genome‐wide association analyses revealed a polygenic basis to variation in bill length with multiple loci detected in or near genes known to affect bill morphology in other birds. Our findings support the hypothesis that divergent selection at microgeographic scales can cause adaptive divergence in the presence of ongoing gene flow.

Mismatch‐induced growth reductions in a clade of Arctic‐breeding shorebirds are rarely mitigated by increasing temperatures - Thomas K. Lameris; Pavel S. Tomkovich; James A. Johnson; R. I. Guy Morrison; Ingrid Tulp; Simeon Lisovski; Lucas DeCicco; Maksim Dementyev; Robert E. Gill; Job ten Horn; Theunis Piersma; Zachary Pohlen; et al. (Global Change Biology, 2022)
In seasonal environments subject to climate change, organisms typically show phenological changes. As these changes are usually stronger in organisms at lower trophic levels than those at higher trophic levels, mismatches between consumers and their prey may occur during the consumers’ reproduction period. While in some species a trophic mismatch induces reductions in offspring growth, this is not always the case. This variation may be caused by the relative strength of the mismatch, or by mitigating factors like increased temperature‐reducing energetic costs. We investigated the response of chick growth rate to arthropod abundance and temperature for six populations of ecologically similar shorebirds breeding in the Arctic and sub‐Arctic (four subspecies of Red Knot Calidris canutus , Great Knot C . tenuirostris and Surfbird C . virgata ). In general, chicks experienced growth benefits (measured as a condition index) when hatching before the seasonal peak in arthropod abundance, and growth reductions when hatching after the peak. The moment in the season at which growth reductions occurred varied between populations, likely depending on whether food was limiting growth before or after the peak. Higher temperatures led to faster growth on average, but could only compensate for increasing trophic mismatch for the population experiencing the coldest conditions. We did not find changes in the timing of peaks in arthropod availability across the study years, possibly because our series of observations was relatively short; timing of hatching displayed no change over the years either. Our results suggest that a trend in trophic mismatches may not yet be evident; however, we show Arctic‐breeding shorebirds to be vulnerable to this phenomenon and vulnerability to depend on seasonal prey dynamics.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Microbial Volatile Organic Compounds from Tempered and Incubated Grain Mediate Attraction by a Primary but Not Secondary Stored Product Insect Pest in Wheat - Taylor Van Winkle; Marco Ponce; Hannah Quellhorst; Alexander Bruce; Chloe E. Albin; Tania N. Kim; Kun Yan Zhu; William R. Morrison (Journal of Chemical Ecology, 2022)
There has been a dearth of research elucidating the behavioral effect of microbially-produced volatile organic compounds on insects in postharvest agriculture. Demonstrating attraction to MVOC’s by stored product insects would provide an additional source of unique behaviorally-relevant stimuli to protect postharvest commodities at food facilities. Here, we assessed the behavioral response of a primary ( Rhyzopertha dominica ) and secondary ( Tribolium castaneum ) grain pest to bouquets of volatiles produced by whole wheat that were untempered, or tempered to 12%, 15%, or 19% grain moisture and incubated for 9, 18, or 27 days. We hypothesized that MVOC’s may be more important for the secondary feeder because they signal that otherwise unusable, intact grains have become susceptible by weakening of the bran. However, contrary to our expectations, we found that the primary feeder, R. dominica , but not T. castaneum was attracted to MVOC’s in a wind tunnel experiment, and in a release-recapture assay using commercial traps baited with grain treatments. Increasing grain moisture resulted in elevated grain damage detected by near-infrared spectroscopy and resulted in small but significant differences in the blend of volatiles emitted by treatments detected by gas chromatography coupled with mass spectrometry (GC–MS). In sequencing the microbial community on the grain, we found a diversity of fungi, suggesting that an assemblage was responsible for emissions. We conclude that R. dominica is attracted to a broader suite of MVOC’s than T. castaneum , and that our work highlights the importance of understanding insect-microbe interactions in the postharvest agricultural supply chain.

Ethics and governance for internet‐based conservation science research - Ruth M. Thompson; Jordan Hall; Chris Morrison; Nicole R. Palmer; David L. Roberts (Conservation Biology, 2021)
Internet‐based research is increasingly important for conservation science and has wide‐ranging applications and contexts, including culturomics, illegal wildlife trade, and citizen science. However, online research methods pose a range of ethical and legal challenges. Online data may be protected by copyright, database rights, or contract law. Privacy rights may also restrict the use and access of data, as well as ethical requirements from institutions. Online data have real‐world meaning, and the ethical treatment of individuals and communities must not be marginalized when conducting internet‐based research. As ethics frameworks originally developed for biomedical applications are inadequate for these methods, we propose that research activities involving the analysis of preexisting online data be treated analogous to offline social science methods, in particular, nondeceptive covert observation. By treating internet users and their data with respect and due consideration, conservationists can uphold the public trust needed to effectively address real‐world issues.

Drought at a coastal wetland affects refuelling and migration strategies of shorebirds - Alexandra M. Anderson; Christian Friis; Cheri L. Gratto-Trevor; Christopher M. Harris; Oliver P. Love; R. I. Guy Morrison; Sean W. J. Prosser; Erica Nol; Paul A. Smith (Oecologia, 2021)
Droughts can affect invertebrate communities in wetlands, which can have bottom-up effects on the condition and survival of top predators. Shorebirds, key predators at coastal wetlands, have experienced widespread population declines and could be negatively affected by droughts. We explored, in detail, the effects of drought on multiple aspects of shorebird stopover and migration ecology by contrasting a year with average wet/dry conditions (2016) with a year with moderate drought (2017) at a major subarctic stopover site on southbound migration. We also examined the effects of drought on shorebird body mass during stopover across 14 years (historical: 1974–1982 and present-day: 2014–2018). For the detailed comparison of two years, in the year with moderate drought we documented lower invertebrate abundance at some sites, higher prey family richness in shorebird faecal samples, lower shorebird refuelling rates, shorter stopover durations for juveniles, and, for most species, a higher probability of making a subsequent stopover in North America after departing the subarctic, compared to the year with average wet/dry conditions. In the 14-year dataset, shorebird body mass tended to be lower in drier years. We show that even short-term, moderate drought conditions can negatively affect shorebird refuelling performance at coastal wetlands, which may carry-over to affect subsequent stopover decisions. Given shorebird population declines and predicted changes in the severity and duration of droughts with climate change, researchers should prioritize a better understanding of how droughts affect shorebird refuelling performance and survival.

Climate Change Implications for Tidal Marshes and Food Web Linkages to Estuarine and Coastal Nekton - Denise D. Colombano; Steven Y. Litvin; Shelby L. Ziegler; Scott B. Alford; Ronald Baker; Myriam A. Barbeau; Just Cebrián; Rod M. Connolly; Carolyn A. Currin; Linda A. Deegan; Justin S. Lesser; Charles W. Martin; et al. (Estuaries and Coasts, 2021)
Climate change is altering naturally fluctuating environmental conditions in coastal and estuarine ecosystems across the globe. Departures from long-term averages and ranges of environmental variables are increasingly being observed as directional changes [e.g., rising sea levels, sea surface temperatures (SST)] and less predictable periodic cycles (e.g., Atlantic or Pacific decadal oscillations) and extremes (e.g., coastal flooding, marine heatwaves). Quantifying the short- and long-term impacts of climate change on tidal marsh seascape structure and function for nekton is a critical step toward fisheries conservation and management. The multiple stressor framework provides a promising approach for advancing integrative, cross-disciplinary research on tidal marshes and food web dynamics. It can be used to quantify climate change effects on and interactions between coastal oceans (e.g., SST, ocean currents, waves) and watersheds (e.g., precipitation, river flows), tidal marsh geomorphology (e.g., vegetation structure, elevation capital, sedimentation), and estuarine and coastal nekton (e.g., species distributions, life history adaptations, predator-prey dynamics). However, disentangling the cumulative impacts of multiple interacting stressors on tidal marshes, whether the effects are additive, synergistic, or antagonistic, and the time scales at which they occur, poses a significant research challenge. This perspective highlights the key physical and ecological processes affecting tidal marshes, with an emphasis on the trophic linkages between marsh production and estuarine and coastal nekton, recommended for consideration in future climate change studies. Such studies are urgently needed to understand climate change effects on tidal marshes now and into the future.

Differential and interacting impacts of invasive plants and white-tailed deer in eastern U.S. forests - David L. Gorchov; Bernd Blossey; Kristine M. Averill; Andrea Dávalos; J. Mason Heberling; Michael A. Jenkins; Susan Kalisz; William J. McShea; Janet A. Morrison; Victoria Nuzzo; Christopher R. Webster; Donald M. Waller (Biological Invasions, 2021)

Impacts of zebra mussels (Dreissena polymorpha) on isotopic niche size and niche overlap among fish species in a mesotrophic lake - Alexandra L. Morrison; Mary A. Thelen; Sarah E. Howe; Kyle D. Zimmer; Brian R. Herwig; David F. Staples; Margaret C. McEachran (Biological Invasions, 2021)

Assessing repellency, movement, and mortality of three species of stored product insects after exposure to deltamethrin-incorporated long-lasting polyethylene netting - D. S. Scheff; A. R. Gerken; W. R. Morrison; J. F. Campbell; F. H. Arthur; K. Y. Zhu (Journal of Pest Science, 2021)

Longitudinal trends of the small mammal community of the Apostle Islands archipelago - Elyse C. Mallinger; Bijit Khadka; Morgan J. Farmer; Megan Morrison; Julie Van Stappen; Timothy R. Van Deelen; Erik R. Olson (Community Ecology, 2021)

Sub‐lethal temperature thresholds indicate acclimation and physiological limits in brook trout Salvelinus fontinalis - Scott M. Morrison; Theresa E. Mackey; Travis Durhack; Jennifer D. Jeffrey; Lilian M. Wiens; Neil J. Mochnacz; Caleb T. Hasler; Eva C. Enders; Jason R. Treberg; Ken M. Jeffries (Journal of Fish Biology, 2020)
The upper thermal tolerance of brook trout Salvelinus fontinalis was estimated using critical thermal maxima (CT max ) experiments on fish acclimated to temperatures that span the species' thermal range (5–25°C). The CT max increased with acclimation temperature but plateaued in fish acclimated to 20, 23 and 25°C. Plasma lactate was highest, and the hepato‐somatic index ( I H ) was lowest at 23 and 25°C, which suggests additional metabolic costs at those acclimation temperatures. The results suggest that there is a sub‐lethal threshold between 20 and 23°C, beyond which the fish experience reduced physiological performance.

Biological Control of the Noxious Weed Angled Onion (Allium triquetrum) Thwarted by Endophytic Bacteria in Victoria, Australia - P. Tehranchian; R. J. Adair; T. T. H. Van; P. D. Morrison; H. Williams; A. C. Lawrie (Australasian Plant Pathology, 2020)

Direct Observation of Low Strain, High Rate Deformation of Cultured Brain Tissue During Primary Blast - Edward W. Vogel; Matthew B. Panzer; Fatima N. Morales; Nevin Varghese; Cameron R. Bass; David F. Meaney; Barclay Morrison (Annals of Biomedical Engineering, 2020)

Attraction, arrestment, and preference by immature Trogoderma variabile and Trogoderma granarium to food and pheromonal stimuli - William R. Morrison; Robert F. Grosdidier; Frank H. Arthur; Scott W. Myers; Michael J. Domingue (Journal of Pest Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Anthropogenic modifications to fire regimes in the wider Serengeti‐Mara ecosystem - James R. Probert; Catherine L. Parr; Ricardo M. Holdo; T. Michael Anderson; Sally Archibald; Colin J. Courtney Mustaphi; Andrew P. Dobson; Jason E. Donaldson; Grant C. Hopcraft; Gareth P. Hempson; Thomas A. Morrison; Colin M. Beale (Global Change Biology, 2019)
Fire is a key driver in savannah systems and widely used as a land management tool. Intensifying human land uses are leading to rapid changes in the fire regimes, with consequences for ecosystem functioning and composition. We undertake a novel analysis describing spatial patterns in the fire regime of the Serengeti‐Mara ecosystem, document multidecadal temporal changes and investigate the factors underlying these patterns. We used MODIS active fire and burned area products from 2001 to 2014 to identify individual fires; summarizing four characteristics for each detected fire: size, ignition date, time since last fire and radiative power. Using satellite imagery, we estimated the rate of change in the density of livestock bomas as a proxy for livestock density. We used these metrics to model drivers of variation in the four fire characteristics, as well as total number of fires and total area burned. Fires in the Serengeti‐Mara show high spatial variability—with number of fires and ignition date mirroring mean annual precipitation. The short‐term effect of rainfall decreases fire size and intensity but cumulative rainfall over several years leads to increased standing grass biomass and fuel loads, and, therefore, in larger and hotter fires. Our study reveals dramatic changes over time, with a reduction in total number of fires and total area burned, to the point where some areas now experience virtually no fire. We suggest that increasing livestock numbers are driving this decline, presumably by inhibiting fire spread. These temporal patterns are part of a global decline in total area burned, especially in savannahs, and we caution that ecosystem functioning may have been compromised. Land managers and policy formulators need to factor in rapid fire regime modifications to achieve management objectives and maintain the ecological function of savannah ecosystems.

Building the Knowledge-to-Action Pipeline in North America: Connecting Ocean Acidification Research and Actionable Decision Support - Jessica N. Cross; Jessie A. Turner; Sarah R. Cooley; Jan A. Newton; Kumiko Azetsu-Scott; R. Christopher Chambers; Darcy Dugan; Kaitlin Goldsmith; Helen Gurney-Smith; Alexandra R. Harper; Elizabeth B. Jewett; Denise Joy; et al. (Frontiers in Marine Science, 2019)

Enhancement of primary production during drought in a temperate watershed is greater in larger rivers than headwater streams - J. D. Hosen; K. S. Aho; A. P. Appling; E. C. Creech; J. H. Fair; R. O. Hall; E. D. Kyzivat; R. S. Lowenthal; S. Matt; J. Morrison; J. E. Saiers; J. B. Shanley; et al. (Limnology and Oceanography, 2019)
Drought is common in rivers, yet how this disturbance regulates metabolic activity across network scales is largely unknown. Drought often lowers gross primary production (GPP) and ecosystem respiration (ER) in small headwaters but by contrast can enhance GPP and cause algal blooms in downstream estuaries. We estimated ecosystem metabolism across a nested network of 13 reaches from headwaters to the main stem of the Connecticut River from 2015 through 2017, which encompassed a pronounced drought. During drought, GPP and ER increased, but with greater enhancement in larger rivers. Responses of GPP and ER were partially due to warmer temperatures associated with drought, particularly in the larger rivers where temperatures during summer drought were > 10°C higher than typical summer baseflow. The larger rivers also had low canopy cover, which allowed primary producers to take advantage of lower turbidity and fewer cloudy days during drought. We conclude that GPP is enhanced by higher temperature, lower turbidity, and longer water residence times that are all a function of low discharge, but ecosystem response in temperate watersheds to these drivers depends on light availability regulated by riparian canopy cover. In larger rivers, GPP increased more than ER during drought, even leading to temporary autotrophy, an otherwise rare event in the typically light‐limited heterotrophic Connecticut River main stem. With climate change, rivers and streams may become warmer and drought frequency and severity may increase. Such changes may increase autotrophy in rivers with broad implications for carbon cycling and water quality in aquatic ecosystems.

Scaling Up From Regional Case Studies to a Global Harmful Algal Bloom Observing System - Clarissa R. Anderson; Elisa Berdalet; Raphael M. Kudela; Caroline K. Cusack; Joe Silke; Eleanor O’Rourke; Darcy Dugan; Molly McCammon; Jan A. Newton; Stephanie K. Moore; Kelli Paige; Steve Ruberg; et al. (Frontiers in Marine Science, 2019)

Investigating hydrogeomorphic floodplain mapping performance with varying DTM resolution and stream order - A. Annis; F. Nardi; R. R. Morrison; F. Castelli (Hydrological Sciences Journal, 2019)

Volatile release, mobility, and mortality of diapausing Halyomorpha halys during simulated shipping movements and temperature changes - Laura J. Nixon; Amy Tabb; William R. Morrison; Kevin B. Rice; Eckehard G. Brockerhoff; Tracy C. Leskey; Chikako van Koten; Stephen Goldson; Michael Rostás (Journal of Pest Science, 2019)

Occurrence of aflatoxins in rice and in cassava (Manihot esculenta) products (meal, bread) produced in Guyana - Donna M. Morrison; David R. Ledoux; Lambert F. B. Chester; Coretta A. N. Samuels (Mycotoxin Research, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Differential Proteomics for Distinguishing Ischemic Stroke from Controls: a Pilot Study of the SpecTRA Project - A. M. Penn; V. Saly; A. Trivedi; M. L. Lesperance; K. Votova; A. M. Jackson; N.S. Croteau; R. F. Balshaw; M. B. Bibok; D. S. Smith; K. K. Lam; J. Morrison; et al. (Translational Stroke Research, 2018)

Neuromotor and cognitive responses of adults with autism spectrum disorder compared to neurotypical adults - Steven Morrison; Cortney N. Armitano; C. Teal Raffaele; Stephen I. Deutsch; Serina A. Neumann; Hope Caracci; Maria R. Urbano (Experimental Brain Research, 2018)

Assessing the Hydrogeomorphic Effects of Environmental Flows using Hydrodynamic Modeling - Angela Gregory; Ryan R. Morrison; Mark Stone (Environmental Management, 2018)

Group II metabotropic glutamate receptor agonist prodrugs LY2979165 and LY2140023 attenuate the functional imaging response to ketamine in healthy subjects - Mitul A. Mehta; Anne Schmechtig; Vasileia Kotoula; Juliet McColm; Kimberley Jackson; Claire Brittain; Sitra Tauscher-Wisniewski; Bruce J. Kinon; Paul D. Morrison; Thomas Pollak; Timothy Mant; Steven C. R. Williams; et al. (Psychopharmacology, 2018)

Enhanced hemoglobin–oxygen unloading in migratory salmonids - Jacelyn J. Shu; Till S. Harter; Phillip R. Morrison; Colin J. Brauner (Journal of Comparative Physiology B, 2018)

Correction to: Genetic and morphological sex identification methods reveal a male-biased sex ratio in the Ivory Gull Pagophila eburnea - Glenn Yannic; Thomas Broquet; Hallvard Strøm; Adrian Aebischer; Christophe Dufresnes; Maria V. Gavrilo; H. Grant Gilchrist; Mark L. Mallory; R. I. Guy Morrison; Brigitte Sabard; Roberto Sermier; Olivier Gilg (Journal of Ornithology, 2018)

Species associations overwhelm abiotic conditions to dictate the structure and function of wood‐decay fungal communities - Daniel S. Maynard; Kristofer R. Covey; Thomas W. Crowther; Noah W. Sokol; Eric W. Morrison; Serita D. Frey; Linda T. A. van Diepen; Mark A. Bradford (Ecology, 2018)
Environmental conditions exert strong controls on the activity of saprotrophic microbes, yet abiotic factors often fail to adequately predict wood decomposition rates across broad spatial scales. Given that species interactions can have significant positive and negative effects on wood‐decay fungal activity, one possibility is that biotic processes serve as the primary controls on community function, with abiotic controls emerging only after species associations are accounted for. Here we explore this hypothesis in a factorial field warming‐ and nitrogen‐addition experiment by examining relationships among wood decomposition rates, fungal activity, and fungal community structure. We show that functional outcomes and community structure are largely unrelated to abiotic conditions, with microsite and plot‐level abiotic variables explaining at most 19% of the total variability in decomposition and fungal activity, and 2% of the variability in richness and evenness. In contrast, taxonomic richness, evenness, and species associations (i.e., co‐occurrence patterns) exhibited strong relationships with community function, accounting for 52% of the variation in decomposition rates and 73% in fungal activity. A greater proportion of positive vs. negative species associations in a community was linked to strong declines in decomposition rates and richness. Evenness emerged as a key mediator between richness and function, with highly even communities exhibiting a positive richness–function relationship and uneven communities exhibiting a negative or null response. These results suggest that community‐assembly processes and species interactions are important controls on the function of wood‐decay fungal communities, ultimately overwhelming substantial differences in abiotic conditions.

From vineyard to winery: a source map of microbial diversity driving wine fermentation - Peter Morrison‐Whittle; Matthew R. Goddard (Environmental Microbiology, 2018)
Summary Humans have been making wine for thousands of years and microorganisms play an integral part in this process as they not only drive fermentation, but also significantly influence the flavour, aroma and quality of finished wines. Since fruits are ephemeral, they cannot comprise a permanent microbial habitat; thus, an age‐old unanswered question concerns the origin of fruit and ferment associated microbes. Here we use next‐generation sequencing approaches to examine and quantify the roles of native forest, vineyard soil, bark and fruit habitats as sources of fungal diversity in ferments. We show that microbial communities in harvested juice and ferments vary significantly across regions, and that while vineyard fungi account for ∼40% of the source of this diversity, uncultivated ecosystems outside of vineyards also prove a significant source. We also show that while communities in harvested juice resemble those found on grapes, these increasingly resemble fungi present on vine bark as the ferment proceeds.

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Chemical ecology of Halyomorpha halys: discoveries and applications - Donald C. Weber; William R. Morrison; Ashot Khrimian; Kevin B. Rice; Tracy C. Leskey; Cesar Rodriguez-Saona; Anne L. Nielsen; Brett R. Blaauw (Journal of Pest Science, 2017)

Attraction of the invasive Halyomorpha halys in its native Asian range to traps baited with semiochemical stimuli - William R. Morrison III; Chang-Gyu Park; Bo Yoon Seo; Yong-Lak Park; Hong Geun Kim; Kevin B. Rice; Doo-Hyung Lee; Tracy C. Leskey (Journal of Pest Science, 2017)

Using a choice experiment and birder preferences to guide bird‐conservation funding - Rochelle Steven; James C. R. Smart; Clare Morrison; J. Guy Castley (Conservation Biology, 2017)
Conservation of biodiversity, including birds, continues to challenge natural‐area managers. Stated‐preference methods (e.g., choice experiment [CE]) are increasingly used to provide data for valuation of natural ecosystems. We used a CE to calculate birders’ willingness to pay for different levels of bioecological attributes (threatened species, endemic species, and diversity) of birding sites with hypothetical entry fees. The CE was delivered at popular birding and avitourism sites in Australia and the United Kingdom. Latent‐class modeling results revealed heterogeneous preferences among birders and correspondingly variable willingness to pay. Four clear groups were apparent: quantity‐driven birders, special‐birds seekers, confused respondents, and price‐is‐no‐object birders. Quantity‐driven birders were attracted to sites that deliver high levels of diversity and endemic species for which they were willing to pay $135 and $66 to visit, respectively, above what they were willing to pay to visit a site with low levels of diversity and few endemic and threatened species . Special‐bird seekers valued threatened species and high levels of endemic species most (willingness to pay $45 and $46, respectively). Confused respondents’ preferences were difficult to determine, but they were the most sensitive to the hypothetical entry fees, unlike the price‐is‐no‐object birders, who were not at all sensitive to cost. Our findings demonstrate that birders are amenable to paying for their preferred birding experience. These payments could provide an alternative source of funding in some avitourism sites on both public and private land. Such alternative revenue streams should be explored and given full consideration in increasingly competitive conservation‐financing environments.

Predation by New Zealand sea lions and Brown Skuas is causing the continued decline of an Eastern Rockhopper Penguin colony on Campbell Island - Kyle W. Morrison; Doug P. Armstrong; Phil F. Battley; Sarah E. Jamieson; David R. Thompson (Polar Biology, 2017)

Transcriptomic effects of adenosine 2A receptor deletion in healthy and endotoxemic murine myocardium - Kevin J. Ashton; Melissa E. Reichelt; S. Jamal Mustafa; Bunyen Teng; Catherine Ledent; Lea M. D. Delbridge; Polly A. Hofmann; R. Ray Morrison; John P. Headrick (Purinergic Signalling, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Predation of Halyomorpha halys (Hemiptera: Pentatomidae) from Web-Building Spiders Associated with Anthropogenic Dwellings - William R. Morrison; Alexandria N. Bryant; Brittany Poling; Nicole F. Quinn; Tracy C. Leskey (Journal of Insect Behavior, 2017)

Multi-generational evaluation of genetic diversity and parentage in captive southern pygmy perch (Nannoperca australis) - Catherine R. M. Attard; Chris J. Brauer; Jacob D. Van Zoelen; Minami Sasaki; Michael P. Hammer; Leslie Morrison; James O. Harris; Luciana M. Möller; Luciano B. Beheregaray (Conservation Genetics, 2016)

Evaluation of an electrostatic particle ionization technology for decreasing airborne pathogens in pigs - Carmen Alonso; Peter C. Raynor; Peter R. Davies; Robert B. Morrison; Montserrat Torremorell (Aerobiologia, 2016)

Genetic and morphological sex identification methods reveal a male-biased sex ratio in the Ivory Gull Pagophila eburnea - Glenn Yannic; Thomas Broquet; Hallvard Strøm; Adrian Aebischer; Christophe Dufresnes; Maria V. Gavrilo; H. Grant Gilchrist; Mark L. Mallory; R. I. Guy Morrison; Brigitte Sabard; Roberto Sermier; Olivier Gilg (Journal of Ornithology, 2016)

Adaptive divergence despite strong genetic drift: genomic analysis of the evolutionary mechanisms causing genetic differentiation in the island fox ( Urocyon littoralis ) - W. Chris Funk; Robert E. Lovich; Paul A. Hohenlohe; Courtney A. Hofman; Scott A. Morrison; T. Scott Sillett; Cameron K. Ghalambor; Jesus E. Maldonado; Torben C. Rick; Mitch D. Day; Nicholas R. Polato; Sarah W. Fitzpatrick; et al. (Molecular Ecology, 2016)
The evolutionary mechanisms generating the tremendous biodiversity of islands have long fascinated evolutionary biologists. Genetic drift and divergent selection are predicted to be strong on islands and both could drive population divergence and speciation. Alternatively, strong genetic drift may preclude adaptation. We conducted a genomic analysis to test the roles of genetic drift and divergent selection in causing genetic differentiation among populations of the island fox ( Urocyon littoralis ). This species consists of six subspecies, each of which occupies a different California Channel Island. Analysis of 5293 SNP loci generated using Restriction‐site Associated DNA ( RAD ) sequencing found support for genetic drift as the dominant evolutionary mechanism driving population divergence among island fox populations. In particular, populations had exceptionally low genetic variation, small N e (range = 2.1–89.7; median = 19.4), and significant genetic signatures of bottlenecks. Moreover, islands with the lowest genetic variation (and, by inference, the strongest historical genetic drift) were most genetically differentiated from mainland grey foxes, and vice versa, indicating genetic drift drives genome‐wide divergence. Nonetheless, outlier tests identified 3.6–6.6% of loci as high F ST outliers, suggesting that despite strong genetic drift, divergent selection contributes to population divergence. Patterns of similarity among populations based on high F ST outliers mirrored patterns based on morphology, providing additional evidence that outliers reflect adaptive divergence. Extremely low genetic variation and small N e in some island fox populations, particularly on San Nicolas Island, suggest that they may be vulnerable to fixation of deleterious alleles, decreased fitness and reduced adaptive potential.

The canalized parental roles of a Eudyptes penguin constrain provisioning and growth of chicks during nutritional stress - Kyle W. Morrison; Neil C. Morrison; Raymond M. Buchheit; Rob Dunn; Phil F. Battley; David R. Thompson (Behavioral Ecology and Sociobiology, 2016)

Establishing the behavioral basis for an attract-and-kill strategy to manage the invasive Halyomorpha halys in apple orchards - William R. Morrison; Doo-Hyung Lee; Brent D. Short; Ashot Khrimian; Tracy C. Leskey (Journal of Pest Science, 2016)

High connectivity in a long-lived high-Arctic seabird, the ivory gull Pagophila eburnea - Glenn Yannic; Jonathan M. Yearsley; Roberto Sermier; Christophe Dufresnes; Olivier Gilg; Adrian Aebischer; Maria V. Gavrilo; Hallvard Strøm; Mark L. Mallory; R. I. Guy Morrison; H. Grant Gilchrist; Thomas Broquet (Polar Biology, 2016)

Behavioral Responses of the Invasive Halyomorpha halys (Stål) (Hemiptera: Pentatomidae) to Light-Based Stimuli in the Laboratory and Field - Tracy C. Leskey; Doo-Hyung Lee; D. Michael Glenn; William R. Morrison (Journal of Insect Behavior, 2015)

Development of twelve microsatellite loci in the red tree corals Primnoa resedaeformis and Primnoa pacifica - C. L. Morrison; M. J. Springmann; K. M. Shroades; R. P. Stone (Conservation Genetics Resources, 2015)

Comparison of low-carbon pathways for California - Geoffrey M. Morrison; Sonia Yeh; Anthony R. Eggert; Christopher Yang; James H. Nelson; Jeffery B. Greenblatt; Raphael Isaac; Mark Z. Jacobson; Josiah Johnston; Daniel M. Kammen; Ana Mileva; Jack Moore; et al. (Climatic Change, 2015)

Ocean and Coastal Acidification off New England and Nova Scotia - Dwight Gledhill; Meredith White; Joe Salisbury; Helmuth Thomas; Ivy Misna; Matthew Liebman; Bill Mook; Jason Grear; Allison Candelmo; R. Christopher Chambers; Christopher Gobler; Christopher Hunt; et al. (Oceanography, 2015)

Behavioral Responses of the Invasive Halyomorpha halys (Stål) to Traps Baited with Stereoisomeric Mixtures of 10,11-Epoxy-1-bisabolen-3-OL - Tracy C. Leskey; Ashot Khrimian; Donald C. Weber; Jeffrey C. Aldrich; Brent D. Short; Doo-Hyung Lee; William R. Morrison (Journal of Chemical Ecology, 2015)

Population dynamics of Eastern Rockhopper Penguins on Campbell Island in relation to sea surface temperature 1942–2012: current warming hiatus pauses a long-term decline - Kyle W. Morrison; Phil F. Battley; Paul M. Sagar; David R. Thompson (Polar Biology, 2015)

Dichloroacetate affects proliferation but not survival of human colorectal cancer cells - L. M. Delaney; N. Ho; J. Morrison; N. R. Farias; D. D. Mosser; B. L. Coomber (Apoptosis, 2015)

Acute survivorship of the deep-sea coral Lophelia pertusa from the Gulf of Mexico under acidification, warming, and deoxygenation - Jay J. Lunden; Conall G. McNicholl; Christopher R. Sears; Cheryl L. Morrison; Erik E. Cordes (Frontiers in Marine Science, 2014)

Using a Gas-Phase Tracer Test to Characterize the Impact of Landfill Gas Generation on Advective-Dispersive Transport of VOCs in the Vadose Zone - Gregg R. Monger; Candice Morrison Duncan; Mark L. Brusseau (Water, Air, & Soil Pollution, 2014)

Higher trophic level prey does not represent a higher quality diet in a threatened seabird: implications for relating population dynamics to diet shifts inferred from stable isotopes - Kyle W. Morrison; Sarah J. Bury; David R. Thompson (Marine Biology, 2014)

Site-specific pre-evaluation of bioremediation technologies for chloroethene degradation - S. S. Patil; E. M. Adetutu; P. J. Sheppard; P. Morrison; I. R. Menz; A. S. Ball (International Journal of Environmental Science and Technology, 2014)

Erratum to: Contribution of allochthonous resources to breeding in a high-arctic avian predator - Jean-Rémi Julien; Pierre Legagneux; Gilles Gauthier; R. I. Guy Morrison; Jean-François Therrien; Joël Bêty (Polar Biology, 2014)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Contribution of allochthonous resources to breeding in a high-arctic avian predator - Jean-Rémi Julien; Pierre Legagneux; Gilles Gauthier; R. I. Guy Morrison; Jean-François Therrien; Joël Bêty (Polar Biology, 2014)

Molecular investigation of bacterial communities on the inner and outer surfaces of peripheral venous catheters - L. Zhang; M. Morrison; G. R. Nimmo; K. S. Sriprakash; S. Mondot; J. R. Gowardman; N. George; N. Marsh; C. M. Rickard (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Sequential extraction procedures for the determination of phosphorus forms in sediment - Changyou Wang; Yong Zhang; Hongli Li; R. John Morrison (Limnology, 2013)

Application of metabolomics to understanding biofilms in water distribution systems: a pilot study - D.J. Beale; R. Barratt; D.R. Marlow; M.S. Dunn; E.A. Palombo; P.D. Morrison; C. Key (Biofouling, 2013)

A Novel Method for Reducing the Effect of Tonic Muscle Activity on the Gamma Band of the Scalp EEG - Judith F. Nottage; Paul D. Morrison; Steve C. R. Williams; Dominic H. ffytche (Brain Topography, 2013)

Population stratification may bias analysis of PGC-1α as a modifier of age at Huntington disease motor onset - Eliana Marisa Ramos; Jeanne C. Latourelle; Ji-Hyun Lee; Tammy Gillis; Jayalakshmi S. Mysore; Ferdinando Squitieri; Alba Di Pardo; Stefano Di Donato; Michael R. Hayden; Patrick J. Morrison; Martha Nance; Christopher A. Ross; et al. (Human Genetics, 2012)

The blood chemical status of Atlantic cod Gadus morhua following capture by jig and demersal longline with differential hook removal methods - J. W. Mandelman; R. A. Morrison; J. M. Cavin; M. A. Farrington (Journal of Fish Biology, 2012)
Common haematological [haematocrit (Hct)], primary (serum cortisol) and secondary (serum glucose and plasma lactate) analytes were utilized to compare blood biochemical status of Gadus morhua captured rapidly by jig with that of G. morhua captured by commercial demersal longline. In general, the physiological status of G. morhua , despite blind hook times, was significantly more disrupted (pronounced haemo‐concentration and significantly elevated concentrations of cortisol, glucose and lactate) following longline capture relative to capture by jig, while no differences were detected among longline‐caught fish as a function of dehooking method (or concomitant extent of overt physical trauma). Blood profiles from the more stressed G. morhua , a possible function of more extended longline hook times, were similar to the most stressed values reported for this species. The results also demonstrate that, although acute blood biochemical status is an effective gauge of relative stress, it does not reflect physical injury status, which has been shown to exert a strong influence on delayed mortality in previous studies in this species. Thus, acute blood chemical status alone may not be the most complete predictor of mortality. Future studies should evaluate physiological repercussions from capture–handling against physical trauma during more extended post‐release periods for this species.

Acinetobacter , Aeromonas and Trichococcus populations dominate the microbial community within urban sewer infrastructure - J. L. VandeWalle; G. W. Goetz; S. M. Huse; H. G. Morrison; M. L. Sogin; R. G. Hoffmann; K. Yan; S. L. McLellan (Environmental Microbiology, 2012)
Summary We evaluated the population structure and temporal dynamics of the dominant community members within sewage influent from two wastewater treatment plants (WWTPs) in Milwaukee, WI. We generated > 1.1 M bacterial pyrotag sequences from the V6 hypervariable region of 16S rRNA genes from 38 influent samples and two samples taken upstream in the sanitary sewer system. Only a small fraction of pyrotags from influent samples (∼ 15%) matched sequences from human faecal samples. The faecal components of the sewage samples included enriched pyrotag populations from Lactococcus and Enterobacteriaceae relative to their fractional representation in human faecal samples. In contrast to the large number of distinct pyrotags that represent faecal bacteria such as Lachnospiraceae and Bacteroides , only one or two unique V6 sequences represented Acinetobacter , Aeromonas and Trichococcus , which collectively account for nearly 35% of the total sewage community. Two dominant Acinetobacter V6 pyrotags (designated Acineto tag 1 and Acineto tag 2) fluctuated inversely with a seasonal pattern over a 3‐year period, suggesting two distinct Acinetobacter populations respond differently to ecological forcings in the system. A single nucleotide change in the V6 pyrotags accounted for the difference in these populations and corresponded to two phylogenetically distinct clades based on full‐length sequences. Analysis of wavelet functions, derived from a mathematical model of temporal fluctuations, demonstrated that other abundant sewer associated populations including Trichococcus and Aeromonas had temporal patterns similar to either Acineto tag 1 or Acineto tag 2. Populations with related temporal fluctuations were found to significantly correlate with the same WWTP variables (5‐day BOD, flow, ammonia, total phosphorous and suspended solids). These findings illustrate that small differences in V6 sequences can represent phylogenetically and ecologically distinct taxa. This work provides insight into microbial community composition and dynamics within the defined environment of urban sewer infrastructure.

Cold-water event of January 2010 results in catastrophic benthic mortality on patch reefs in the Florida Keys - M. A. Colella; R. R. Ruzicka; J. A. Kidney; J. M. Morrison; V. B. Brinkhuis (Coral Reefs, 2012)

Post-emplacement fluids and pluton thermobarometry: Mount Stuart batholith, Washington Cascades - J. Lawford Anderson; Jean Morrison; Scott R. Paterson (International Geology Review, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Mercury in the Great Lakes region: bioaccumulation, spatiotemporal patterns, ecological risks, and policy - David C. Evers; James G. Wiener; Niladri Basu; R. A. Bodaly; Heather A. Morrison; Kathryn A. Williams (Ecotoxicology, 2011)

Randomized, controlled, double-blind trial of taranabant for smoking cessation - Mary F. Morrison; Paulette Ceesay; Ira Gantz; Keith D. Kaufman; Christopher R. Lines (Psychopharmacology, 2010)

Regulation of seed yield and agronomic characters by photoperiod sensitivity and growth habit genes in soybean - Elroy R. Cober; Malcolm J. Morrison (Theoretical and Applied Genetics, 2010)

Nutrient Pollution in Laucala Bay, Fiji Islands - Sarabjeet Singh; W. G. L. Aalbersberg; R. J. Morrison (Water, Air, & Soil Pollution, 2009)

Nutrient Limitation on Phytoplankton Growth in the Upper Barataria Basin, Louisiana: Microcosm Bioassays - Ling Ren; Nancy N. Rabalais; R. Eugene Turner; Wendy Morrison; Warren Mendenhall (Estuaries and Coasts, 2009)

Effect of PCR amplicon size on assessments of clone library microbial diversity and community structure - Julie A. Huber; Hilary G. Morrison; Susan M. Huse; Phillip R. Neal; Mitchell L. Sogin; David B. Mark Welch (Environmental Microbiology, 2009)
Summary PCR‐based surveys of microbial communities commonly use regions of the small‐subunit ribosomal RNA (SSU rRNA) gene to determine taxonomic membership and estimate total diversity. Here we show that the length of the target amplicon has a significant effect on assessments of microbial richness and community membership. Using operational taxonomic unit (OTU)‐ and taxonomy‐based tools, we compared the V6 hypervariable region of the bacterial SSU rRNA gene of three amplicon libraries of c. 100, 400 and 1000 base pairs (bp) from each of two hydrothermal vent fluid samples. We found that the smallest amplicon libraries contained more unique sequences, higher diversity estimates and a different community structure than the other two libraries from each sample. We hypothesize that a combination of polymerase dissociation, cloning bias and mispriming due to secondary structure accounts for the differences. While this relationship is not linear, it is clear that the smallest amplicon libraries contained more different types of sequences, and accordingly, more diverse members of the community. Because divergent and lower abundant taxa can be more readily detected with smaller amplicons, they may provide better assessments of total community diversity and taxonomic membership than longer amplicons in molecular studies of microbial communities.

Expanding the Global Network of Protected Areas to Save the Imperiled Mediterranean Biome - EMMA C. UNDERWOOD; KIRK R. KLAUSMEYER; ROBIN L. COX; SYLVIA M. BUSBY; SCOTT A. MORRISON; M. REBECCA SHAW (Conservation Biology, 2009)
Global goals established by the Convention on Biological Diversity stipulate that 10% of the world's ecological regions must be effectively conserved by 2010. To meet that goal for the mediterranean biome, at least 5% more land must be formally protected over the next few years. Although global assessments identify the mediterranean biome as a priority, without biologically meaningful analysis units, finer‐resolution data, and corresponding prioritization analysis, future conservation investments could lead to more area being protected without increasing the representation of unique mediterranean ecosystems. We used standardized analysis units and six potential natural vegetation types stratified by 3 elevation zones in a global gap analysis that systematically explored conservation priorities across the mediterranean biome. The highest levels of protection were in Australia, South Africa, and California‐Baja California (from 9–11%), and the lowest levels of protection were in Chile and the mediterranean Basin ( 30% conversion and suggest that these assemblages be elevated to high‐priority status in future conservation efforts.

Nitrogen enrichment modifies plant community structure via changes to plant–soil feedback - P. Manning; S. A. Morrison; M. Bonkowski; R. D. Bardgett (Oecologia, 2008)

Immunohistochemical staining for tilapia and human insulin demonstrates that a tilapia transgenic for humanized insulin is a mosaic - James R. Wright; Jaime Snowdon; Olga Hrytsenko; Carol M. Morrison; Bill Pohajdak (Transgenic Research, 2008)

Immunohistochemical detection of anterior gradient‐2 in the gills of amoebic gill disease‐affected Atlantic salmon, Salmo salar L. - R N Morrison; B F Nowak (Journal of Fish Diseases, 2008)

Detection of serum anti‐ Neoparamoeba spp. antibodies in amoebic gill disease‐affected Atlantic salmon Salmo salar - B. N. Vincent; B. F. Nowak; R. N. Morrison (Journal of Fish Biology, 2008)
Amoebic gill disease (AGD)‐affected Atlantic salmon Salmo salar sometimes developed a serum‐antibody response to wild‐type Neoparamoeba spp. Five of 103 AGD‐affected S. salar sampled possessed detectable antibodies that bound wild‐type Neoparamoeba spp. western blotting revealed two distinctly different binding profiles.

Generation and characterization of recombinant feline β-galactosidase for preclinical enzyme replacement therapy studies in GM1 gangliosidosis - Tatiana I. Samoylova; Douglas R. Martin; Nancy E. Morrison; Misako Hwang; Anna M. Cochran; Alexandre M. Samoylov; Henry J. Baker; Nancy R. Cox (Metabolic Brain Disease, 2008)

Development of a diagnostic PCR to detect Neoparamoeba perurans , agent of amoebic gill disease - N D Young; I Dyková; B F Nowak; R N Morrison (Journal of Fish Diseases, 2008)
The recent description of Neoparamoeba perurans as an aetiological agent of amoebic gill disease (AGD) advanced our understanding of the condition and has forced a re‐evaluation of methods used for the diagnosis of AGD. Currently, there are no tools available that are both specific for N. perurans and suitable for a routine diagnostic procedure. Therefore, in this study we describe an assay to detect N. perurans . The assay, which utilizes PCR to amplify the N. perurans 18S rRNA gene, was shown to be specific and highly sensitive. Neoparamoeba perurans was detected in both gill samples and primary isolates of non‐cultured gill‐derived amoebae obtained during necropsy or biopsy from AGD‐affected Atlantic salmon, Salmo salar L. The PCR‐based assay provides a simple, flexible tool that will be a useful addition to the diagnostic repertoire for AGD. It may also be used for the genotypic screening of trophozoites during culture and could facilitate further epidemiological and ecological studies of AGD.

Spatial and Temporal Variability in Dissolved Inorganic Nitrogen Fluxes at the Sediment–Water Interface in Lake Illawarra, Australia - Wenchuan Qu; R. J. Morrison; R. J. West; Chenwei Su (Water, Air, & Soil Pollution, 2007)

Multicenter retrospective development and validation of a clinical prediction rule for nosocomial invasive candidiasis in the intensive care setting - L. Ostrosky-Zeichner; C. Sable; J. Sobel; B. D. Alexander; G. Donowitz; V. Kan; C. A. Kauffman; D. Kett; R. A. Larsen; V. Morrison; M. Nucci; P. G. Pappas; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

The effects of age and streptozotocin diabetes on the sympathetic innervation in the rat penis - J. F. B. Morrison; D. J. Pallot; R. Sheen; S. Dhanasekaran; E. P. K. Mensah-Brown (Molecular and Cellular Biochemistry, 2007)

In vitro interactions between Neoparamoeba spp. and salmonid leucocytes; the effect of parasite sonicate on anterior kidney leucocyte function - K. Gross; S. Alcorn; A. Murray; R. Morrison; B. Nowak (Journal of Fish Biology, 2006)
Sonicated Neoparamoeba spp. (Nspp) did not affect the in vitro respiratory burst response of leucocytes isolated from Atlantic salmon Salmo salar , rainbow trout Oncorhynchus mykiss and chinook salmon Oncorhynchus tshawytscha anterior kidneys ( P > 0·05). Atlantic salmon and chinook salmon leucocytes pre‐incubated with the parasites, however, responded to phorbol myristate acetate (PMA) stimulation with a greater response compared to cells incubated with PMA on its own ( P

Amoebic gill disease (AGD)‐affected Atlantic salmon, Salmo salar L., are resistant to subsequent AGD challenge - B N Vincent; R N Morrison; B F Nowak (Journal of Fish Diseases, 2006)
There is inconsistent evidence of resistance of Atlantic salmon, Salmo salar L., to amoebic gill disease (AGD). Here, evidence is presented that demonstrates that Atlantic salmon exposed and subsequently challenged with AGD are more resistant than naïve control fish. Seventy‐three per cent of Atlantic salmon previously exposed to AGD survived to day 35 post‐challenge compared with 26% exposed to Neoparamoeba sp. for the first time, yet the gill pathology of surviving naïve control or previously exposed fish was not significantly different. Development of resistance to AGD is associated with anti‐ Neoparamoeba sp. antibodies that were detectable in serum of 50% of surviving Atlantic salmon previously exposed to AGD. However, anti‐ Neoparamoeba sp. antibodies were not detectable in cutaneous mucus of resistant fish. Increased resistance of Atlantic salmon after secondary Neoparamoeba sp. infection and detection of specific serum antibodies provides support for the development of a vaccine for AGD.

Age-related differences in inter-digit coupling during finger pinching - Justin Keogh; S. Morrison; R. Barrett (European Journal of Applied Physiology, 2006)

Coordination of head and trunk accelerations during walking - J. J. Kavanagh; S. Morrison; R. S. Barrett (European Journal of Applied Physiology, 2005)

The effect of β‐glucan administration on macrophage respiratory burst activity and Atlantic salmon, Salmo salar L., challenged with amoebic gill disease – evidence of inherent resistance - A R Bridle; C G Carter; R N Morrison; B F Nowak (Journal of Fish Diseases, 2005)
Previous studies have demonstrated that β ‐glucans stimulate Atlantic salmon, Salmo salar L., head kidney macrophages both in vitro and in vivo and increase protection against various pathogens. Based on our previous work that showed potent immunostimulatory CpG motif‐containing oligodeoxynucleotides increased resistance to amoebic gill disease (AGD), the present study investigated the immunostimulatory effects of three commercial β ‐glucan‐containing feeds and their ability to increase resistance to AGD. All three commercial β ‐glucans were able to stimulate the respiratory burst activity of Atlantic salmon head kidney macrophages in vitro , albeit at different times and concentrations. However, dietary incorporation of the β ‐glucans was unable to stimulate the in vivo respiratory burst activity of head kidney macrophages, or serum lysozyme production, and did not increase resistance against AGD. However, this trial showed for the first time that a small subpopulation of Atlantic salmon subjected to a severe AGD infection was able to resist becoming heavily infected and furthermore survive the challenge.

Changes in the innate immune response of Atlantic salmon, Salmo salar L., exposed to experimental infection with Neoparamoeba sp. - K A Gross; M D Powell; R Butler; R N Morrison; B F Nowak (Journal of Fish Diseases, 2005)
An experiment was conducted to determine the effect of Neoparamoeba sp. infection on the innate immune responses of Atlantic salmon. Atlantic salmon were experimentally infected with Neoparamoeba sp. and serially sampled 0, 1, 4, 6, 8 and 11 days post‐exposure (dpe). Histological analysis of infected fish gill arches identified the presence of characteristic amoebic gill disease lesions as early as 1 dpe with a steady increase in the number of affected gill filaments over time. Immune parameters investigated were anterior kidney phagocyte function (respiratory burst, chemotaxis and phagocytosis) and total plasma protein and lysozyme. In comparison with non‐exposed control fish basal respiratory burst responses were suppressed at 8 and 11 dpe, while phorbol myristate acetate‐stimulated activity was significantly suppressed at 11 dpe. Variable differences in phagocytic activity and phagocytic rate following infection were identified. There was an increase in the chemotactic response of anterior kidney macrophages isolated from exposed fish relative to control fish at 8 dpe. Total protein and lysozyme levels were not affected by Neoparamoeba sp. exposure.

Novel microbial diversity adherent to plant biomass in the herbivore gastrointestinal tract, as revealed by ribosomal intergenic spacer analysis and rrs gene sequencing - Ross Larue; Zhongtang Yu; Victoria A. Parisi; Adrian R. Egan; Mark Morrison (Environmental Microbiology, 2005)
Summary It is well recognized that a dynamic biofilm develops upon plant biomass in the herbivore gastrointestinal tract, but this component of the microbiome has not previously been specifically sampled, or directly compared with the biodiversity present in the planktonic fraction of digesta. In this study, the digesta collected from four sheep fed two different diets was separated into three fractions: the planktonic phase, and the microbial populations either weakly or tightly adherent to plant biomass. The community DNA prepared from each fraction was then subjected to both ribosomal intergenic spacer analysis (RISA) and denaturing gradient gel electrophoresis (DGGE). Both types of analysis showed that dietary factors influence community structure, and that the adherent fractions produced more complex profiles. The RIS‐clone libraries prepared from the planktonic and adherent populations were then subjected to restriction fragment length polymorphism (RFLP) and DNA sequence analyses, which resulted in a far greater degree of discrimination among the fractions. Although many of the sequenced clones from the adherent populations were assigned to various clusters within the low G+C Gram‐positive bacteria, the clone libraries from animals consuming an all‐grass diet were largely comprised of novel lineages of Clostridium , while in animals consuming the starch‐containing diet, Selenomonas and Ruminococcus spp. were the dominant low G+C Gram‐positive bacteria. Additionally, the libraries from hay‐fed animals also contained clones most similar to asaccharolytic Clostridia, and other Gram‐positive bacteria that specialize in the transformation of plant phenolic compounds and the formation of cinnamic, phenylacetic and phenylpropionic acids. These results reveal, for the first time, the phylogeny of adherent subpopulations that specialize in the transformation of plant lignins and other secondary compounds, which potentiate polysaccharide hydrolysis by other members of the biofilm.

Diagenetic stoichiometry and benthic nutrient fluxes at the sediment–water interface of Lake Illawarra, Australia - Wenchuan Qu; R. J. Morrison; R. J. West; Chenwei Su (Hydrobiologia, 2005)

Metabolic correlates of leg length in breeding arctic shorebirds: the cost of getting high - Ralph V. Cartar; R. I. Guy Morrison (Journal of Biogeography, 2005)
Aim We test the hypothesis that tarsus length in all shorebirds breeding in the Canadian arctic shows an evolutionary response to average metabolic stress encountered across the breeding range, such that birds nesting in metabolically stressful environments have relatively shorter legs. Longer‐legged birds living in colder environments will experience greater metabolic costs because their torsos are elevated farther away from the ground's wind‐dampening boundary layer. Methods We use weather data (temperature, wind speed, global solar radiation) from 27 arctic weather stations measured over 37 years, and a previously published model of heat transfer, to characterize the metabolic harshness over the breeding season of the ranges of each of the 17 shorebirds of the family Charadriidae nesting in the Canadian arctic. Results After controlling for the lengths of two other body extremities (wing and bill), there was a significant negative relationship between tarsus length and mean metabolic harshness. This result was obtained whether species were treated as independent data points, or in a comparative analysis using standardized independent contrasts. Main conclusions We support a unique extension of Allen's rule: body‐supporting appendages of homeotherms may be shorter in colder environments so as to take advantage of a boundary layer effect, thereby reducing metabolic costs.

Augmented visual feedback increases finger tremor during postural pointing - J. Keogh; S. Morrison; R. Barrett (Experimental Brain Research, 2004)

The induction of laboratory‐based amoebic gill disease revisited - R N Morrison; P B B Crosbie; B F Nowak (Journal of Fish Diseases, 2004)
Previous work in our laboratory defined a method of inducing laboratory‐based amoebic gill disease (AGD) in Atlantic salmon, Salmo salar L. Gills of AGD‐affected fish were scraped and the debris placed into fish‐holding systems, eliciting AGD in naïve Atlantic salmon. While this method is consistently successful in inducing AGD, variability in the kinetics and severity of infections has been observed. It is believed that the infections are influenced by inherently variable viability of post‐harvest amoeba trophozoites. Here, a new method of experimental induction of AGD is presented that redefines the infection model including the minimum infective dose. Amoebae were partially purified from the gills of AGD‐affected Atlantic salmon. Trophozoites were characterized by light microscopy and immunocytochemistry and designated Neoparamoeba sp., possibly Neoparamoeba pemaquidensis . Cells were placed into experimental infection systems ranging in concentration from 0 to 500 cells L −1 . AGD was detected by gross and histological examination in fish held in all systems inoculated with amoebae. The number of gross and histological AGD lesions per gill was proportional to the inoculating concentration of amoebae indicating that the severity of disease is a function of amoeba density in the water column. The implications of these observations are discussed in the context of the existing AGD literature base as well as Atlantic salmon farming in south‐eastern Tasmania.

Effects of age and streptozotocin-induced diabetes on biogenic amines in rat tail artery - J.F.B. Morrison; S. Dhanasekaran; R. Sheen (Molecular and Cellular Biochemistry, 2004)

Detection of enterovirus capsid protein VP1 in myocardium from cases of myocarditis or dilated cardiomyopathy by immunohistochemistry: further evidence of enterovirus persistence in myocytes - Hongyi Zhang; Yanwen Li; Dougal R. McClean; Peter J. Richardson; Richard Florio; Mary Sheppard; Karen Morrison; Najma Latif; Michael J. Dunn; Leonard C. Archard (Medical Microbiology and Immunology, 2004)

Host Location Behavior in a Parasitoid of Imported Fire Ants - Lloyd W. Morrison; Joshua R. King (Journal of Insect Behavior, 2004)

Atlantic salmon, Salmo salar L., previously infected with Neoparamoeba sp. are not resistant to re‐infection and have suppressed phagocyte function - K A Gross; R N Morrison; R Butler; B F Nowak (Journal of Fish Diseases, 2004)
Previous studies have indicated that Atlantic salmon, Salmo salar L., affected by amoebic gill disease (AGD) are resistant to re‐infection. These observations were based upon a comparison of gross gill lesion abundance between previously infected and naïve control fish. Anecdotal evidence from Atlantic salmon farms in southern Tasmania suggests that previous infection does not protect against AGD as indicated by a lack of temporal change in freshwater bathing intervals. Experiments were conducted to determine if previous infection of Atlantic salmon with Neoparamoeba sp. would provide protection against challenge and elucidate the immunological basis of any protection. Atlantic salmon were infected with Neoparamoeba sp. for 12 days then treated with a 4‐h freshwater bath. Fish were separated into two groups and maintained in either sea water or fresh water for 6 weeks. Fish were then transferred to one tank with a naïve control group and challenged with Neoparamoeba sp. Fish kept in sea water had lower mortality rates compared with first time exposed and freshwater maintained fish, however, these data are believed to be biased by ongoing mortalities during the seawater maintenance phase. Phagocyte function decreased over exposure time and freshwater maintained fish demonstrated an increased ability to mount a specific immune response. These results suggest that under the challenge conditions herein described, antigen exposure via infection does not induce protection to subsequent AGD.

Structure and enzymatic removal of the chorion of embryos of the Nile tilapia - C. M. Morrison; B. Pohajdak; M. Henry; J. R. Wright (Journal of Fish Biology, 2003)
Dechorionation or partial digestion of the egg chorion is necessary for introducing embryonic stem cells into blastulas for chimera production and for harvesting blastulas. Several methods to digest the Nile tilapia Oreochromis niloticus chorion were tried and it was found that the chorions of most clutches of eggs were digested in −1 pronase P6911 in 10% Ca/Mg free HBSS. The chorion of Nile tilapia possesses multiple lamellae as found in most teleost species that have been studied. It was found to be thinner than that of medaka Oryzias latipes and thicker than that of zebrafish Danio rerio . During natural hatching the chorion was digested from the inner surface, and tail movements helped to break the remaining chorion; however, chorion digestion has to be complete for experimental dechorionation, because digestion starts at the external surface. The zona radiata externa remained intact after experimental digestion with hatching media but was disrupted by pronase. Embryos dechorionated at the cleavage or blastula stage only survived for 2 or 3 days, but some dechorionated at the gastrula stage or early segmentation stage developed until the natural hatching time. If the chorion was partially digested at the cleavage or blastula stage, some embryos survived to hatch.

A Computational Model of Direct Interstitial Infusion of Macromolecules into the Spinal Cord - Malisa Sarntinoranont; Rupak K. Banerjee; Russell R. Lonser; Paul F. Morrison (Annals of Biomedical Engineering, 2003)

Inorganic nutrient and oxygen fluxes across the sediment–water interface in the inshore macrophyte areas of a shallow estuary (Lake Illawarra, Australia) - Wenchuan Qu; R. J. Morrison; R. J. West (Hydrobiologia, 2003)

Identification and characterization of a novel murine beta-defensin-related gene - Gillian M. Morrison; Mark Rolfe; Fiona M. Kilanowski; Sally H. Cross; Julia R. Dorin (Mammalian Genome, 2002)

The immuno‐adjuvant effect of carp interleukin‐1 beta on the humoral immune response of barramundi, Lates calcarifer (Bloch) - A R Bridle; P B B Crosbie; R N Morrison; J Kwang; B F Nowak (Journal of Fish Diseases, 2002)

MUSCLE-DERIVED CD45−SCA-1+C-KIT− PROGENITOR CELLS GIVE RISE TO SKELETAL MUSCLE MYOTUBES IN VITRO - CASSANDRE L. ROYER; JONATHAN C. HOWELL; PAUL R. MORRISON; EDWARD F. SROUR; MERVIN C. YODER (In Vitro Cellular & Developmental Biology - Animal, 2002)

Conservation Value of Private Lands for Crested Caracaras in Florida - Joan L. Morrison; Stephen R. Humphrey (Conservation Biology, 2001)
In southcentral Florida, where agricultural lands are being converted rapidly to urban development, much of the remaining nonurban habitat occurs on privately owned cattle ranches. We studied the Crested Caracara ( Caracara cheriway ), a threatened bird of prey, to learn the role of private lands in sustaining the population. We investigated patterns of distribution and reproductive activity of breeding pairs of caracaras in relation to patterns of land ownership and use. Eighty‐two percent of 73 active nest sites found were on privately owned cattle ranches. We rarely found breeding pairs on publicly owned lands, most of which are managed as natural areas (no agricultural production and limited livestock grazing) to support native plant and animal communities. In 46 breeding areas with 4 years of known histories of occupancy and reproduction, pairs nesting on lands where the major land use was cattle ranching exhibited higher rates of breeding‐area occupancy, attempted breeding during more years, initiated egg laying earlier, exhibited higher nesting success, and attempted a second brood after successfully fledging a first brood more often than pairs nesting on lands managed as natural areas. Compositional analysis suggested nonrandom selection of habitats by breeding pairs of caracaras in their establishment of a home range in the current landscape of southcentral Florida. Compared with random areas and available habitat in the overall study area, caracara home ranges had higher proportions of improved pasture and lower proportions of forest, woodland, oak scrub, and marsh. Which management activities favor and do not favor caracaras is uncertain, and hypotheses should be formulated and tested to guide future conservation applications. Particular grazing and fire management practices on privately and publicly owned lands may affect the structure of vegetation and prey communities in ways that influence caracaras. Or, replacement of native by exotic grasses may retain structurally suitable plant communities, whereas fertilization and grazing may increase productivity and nutrient cycling in ways that favor caracaras. Given continued conversion of natural habitats and agricultural lands to urban development, it is important to recognize that cattle ranches may provide important resources for wildlife conservation. Although cattle ranching is not likely to benefit all species historically associated with the native prairie ecosystem in Florida, finding ways to retain this land use may be important for the conservation of Florida's population of Crested Caracaras and other organisms of Florida's dry prairies.

Leftward shift in the acquisition of cocaine self-administration in isolation-reared rats: relationship to extracellular levels of dopamine, serotonin and glutamate in the nucleus accumbens and amygdala-striatal FOS expression - Simon R. Howes; Jeffrey W. Dalley; Caroline H. Morrison; Trevor W. Robbins; Barry J. Everitt (Psychopharmacology, 2000)

The influence of fire frequency on arbuscular mycorrhizal colonization in the shrub Dillwynia retorta (Wendland) Druce (Fabaceae) - F. R. Torpy; David A. Morrison; B. J. Bloomfield (Mycorrhiza, 1999)

A study of the histology of the digestive tract of the Nile tilapia - C. M. Morrison; J. R. Wright (Journal of Fish Biology, 1999)
The digestive tract of Oreochromis niloticus is described, in order to resolve discrepancies found between previous accounts. Two types of goblet cells were found in the oesophagus, which differed in size, and in staining characteristics with periodic acid‐Schiff and alcian blue. A region with tubular glands consisting of large mucous cells was continuous from the entry of the oesophagus, across the anterior part of the stomach to the pyloric valve, essentially providing a bypass circumventing the sac‐like portion of the stomach. This region, which is lined with striated muscle, may be a means of disposing of unwanted material, either by regurgitating it, or by passing it rapidly along to the intestine. Large mucus cells in the tubular glands and the neck cells of the gastric glands probably protect the mucosa from the very acid contents of the stomach. An ileorectal valve was present. There is therefore a separate intestine and rectum in O. niloticus , as in most teleosts.

Litter decomposition rates in Canadian forests - T. R. Moore; J. A. Trofymow; B. Taylor; C. Prescott; C. Camiré; L. Duschene; J. Fyles; L. Kozak; M. Kranabetter; I. Morrison; M. Siltanen; S. Smith; et al. (Global Change Biology, 1999)
The effect of litter quality and climate on the rate of decomposition of plant tissues was examined by the measurement of mass remaining after 3 years’ exposure of 11 litter types placed at 18 forest sites across Canada. Amongst sites, mass remaining was strongly related to mean annual temperature and precipitation and amongst litter types the ratio of Klason lignin to nitrogen in the initial tissue was the most important litter quality variable. When combined into a multiple regression, mean annual temperature, mean annual precipitation and Klason lignin:nitrogen ratio explained 73% of the variance in mass remaining for all sites and tissues. Using three doubled CO 2 GCM climate change scenarios for four Canadian regions, these relationships were used to predict increases in decomposition rate of 4–7% of contemporary rates (based on mass remaining after 3 years), because of increased temperature and precipitation. This increase may be partially offset by evidence that plants growing under elevated atmospheric CO 2 concentrations produce litter with high lignin:nitrogen ratios which slows the rate of decomposition, but this change will be small compared to the increased rate of decomposition derived from climatic changes.

Mouse beta defensin-1 is a functional homolog of human beta defensin-1 - Gillian M. Morrison; Donald J. Davidson; Fiona M. Kilanowski; Duncan W. Borthwick; Ken Crook; Alison I. Maxwell; John R.W. Govan; Julia R. Dorin (Mammalian Genome, 1998)

Sequence diversity present within the 5′ upstream regions of BoLA class I genes - N. Barker; John R. Young; W. Ivan Morrison; Shirley A. Ellis (Immunogenetics, 1997)

Characterization of volume-sensitive organic osmolyte efflux and anion current in Xenopus oocytes - M. Hand; R. Morrison; K. Strange (The Journal of Membrane Biology, 1997)

The identification of novel sequences expressed in the mouse notochord - J. C. Sowden; K. Morrison; W. Putt; R. Beddington; Y. H. Edwards (Mammalian Genome, 1997)

Evaluation of the mutagenic potential of bacterial polychlorinated biphenyl biodegradation products - G. S. Sayler; M. C. Reid; B. K. Perkins; R. M. Pagni; R. L. Smith; T. K. Rao; J. L. Epler; W. D. Morrison; R. DuFrain (Archives of Environmental Contamination and Toxicology, 1982)

The changing role of soil pests attacking potato tubers - H. E. Morrison; L. G. Gentner; R. F. Koontz; R. W. Every (American Journal of Potato Research, 1967)

The effect of storage temperature on reducing sugars, pH, and phosphorylase enzyme activity in potato tubers - R. B. Hyde; J. W. Morrison (American Journal of Potato Research, 1964)